Updating Curricula of Iraqi Higher Education Institutions & SDGs Achievement - Al-Rubaie, . Mahmoud Dawood Selman (مجلة الشرق الأوسط للعلوم التربوية والنفسية, 2024)
Education, being an essential requirement to achieve the Sustainable Development Goals (SDGs), curricula life. Accordingly, most Higher Education Institutions have paid much attention to modernize curricula due to their positive impact on the progress of societies, in addition to identifying and internalizing the role of employees in the accomplishment of SDGs. They should be aware that their environment is the shelter that they are assumed to protect and preserve. Therefore, the goals related to people’s environment have been widely explored in the updated curricula as they work on meeting the learners’ needs, their concerns, and developing meanwhile their skills of different directions. Nonetheless, the curricula of some Iraqi Higher Education Institutions still do not include materials that are consistent with the learners’ tendencies and their abilities as well as the essential requirements of society. Hence, these curricula have failed to achieve the main strategies of learning because they have been concentrating on specific topics that only assist students to shift from one study stage to another. The process of updating the curricula of Iraqi Higher Education Institutions, as per the researcher’s viewpoint, is considered as part of the UN Sustainable Development Goals, when applied, whether now or in the future, they shall change the role of academics as well as students, creating meanwhile some type of link between educational, productive and service institutions, and thus connecting education with life and acquisition of labor skills, being essential factors that lead to promoting the concept of curriculum. The researcher has adopted a descriptive approach focusing in his survey on a sample of 68, he has come up with the following conclusions: Most updated items of the curricula assist in achieving the Sustainable Development Goals. Higher Education Institutions participate in supporting and encouraging transfer of appropriate advanced technologies so as to achieve Sustainable Development Goals. Besides, we have come up with the following recommendations: It is quite necessary to update the curricula according to their objectives and outcomes for the purpose of achieving SDGs in face of current and future challenges. Establishing an infrastructure for financing and implementing curricula that could enable students to contribute in achieving the Sustainable Development Goals. integrating the SDGs with the environmental, social, cultural and scientific objectives.